RESEARCH OF POSSIBILITIES OF LASER POLISHING OF THE SURFACE OF ALUMINUM - Bulavskis, Kevins; Adijāns, Imants; Lazov, Lyubomir (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2021)
The report considers the possibility of reducing the roughness after laser polishing of Aluminum plates. A CHANXAN CX-20G fiber laser with a wavelength of 1064 nm is used for the research. As a result of the experiment, 4 matrices were marked with a fiber laser on 3 samples for each series of the experiment. Then, using a multifunctional microscope, the roughness of the treated and untreated aluminum surface was measured. At the end of the research, conclusions were made about the changes in roughness in the course of this experiment.